Is there a significant change in the price transmission between producer and retail prices within the British Pork industry? - PAPARAS, Dimitrios; PICKERING, Thomas; TREMMA, Ourania; AGUIAR, Líis (Turkish Economic Review, 2018)
Abstract. The purpose of this study is to examine price transmission between the producer and retail in the UK pork industry. It aims to find the direction of causality in the long and short-run, and whether there is a long-run relationship between producer and retail prices. This study used monthly time series data for producer and retail prices ranging from 1988-2016. Econometric tests were used such as the Augmented Dickey-Fuller (1979) and Phillips-Perron (1988) Unit Root tests; Bai-Perron (1998) Unit Root test allowing for multiple structural breaks; Johansen (1991) and Engle-Granger (1987) Co-integration tests; Granger (1988) Causality, and the Error Correction Model showing the speed of recovery in the long-run after a shock. The results of the Unit Root tests found both producer and retail prices to be integrated of order one I(1). Three structural breaks were found occurring in the years of 1996, 2002 and 2012. The Co-integration tests found that there is one long-run relationship between producer and retail prices. The Error Correction Model showed the return to a new equilibrium after a shock was 9% per month totalling over 11 months for a full recovery from a shock. The Granger (1988) Causality test indicated that producer prices do Granger cause retail prices in the short-run. In this study the latest econometric techniques were used including structural breaks which some previous studies overlooked. This study into the producer and retail prices in the UK pork industry is the latest study of this kind since the Brexit decision. Keywords. Price transmission, Producer, Retail, Pork, Unit Root, Bai-Perron co-integration, Structural breaks, Error correction model, Causality, Brexit. JEL. L60, L70, L80.